(Epi)Genetic Analyses of Age-Related Macular Degeneration: Case-control and Discordant Twin Studies - Hutchinson, John N. (Hum Hered, 2014)
BACKGROUND/AIMS: Phenotypic discordance in monozygotic (MZ) twin pairs can have an epigenetic or genetic basis. Although age-related macular degeneration (AMD) has a strong genetic component, few studies have addressed it’s epigenetic basis. METHODS: Using SNP arrays, we evaluated differences in copy-number variation (CNV) and allele-specific methylation (ASM) patterns (via methyl-sensitive restriction enzyme digestion of DNA) in MZ twin pairs from the US Twin Study of AMD. Further analyses examined the relationship between ASM and CNVs with AMD by both case/control analysis of ASM at candidate regions and by analysis of ASM and CNVs in twins discordant for AMD. RESULTS: The frequency of ASM sites differ between cases and controls in regions surrounding the AMD-candidate genes CFH, C2 and CFB. While ASM patterns show substantial dependence on local sequence polymorphisms, we observe dissimilar patterns of ASM between MZ twins. Genes closest to sites where discordant MZ twins have dissimilar patterns of ASM are enriched for genes implicated in gliosis, a process associated with neovascular AMD. Similar twin-based analyses revealed no AMD associated CNVs. CONCLUSIONS: Our results provide evidence of epigenetic influences beyond the known genetic susceptibility and implicate inflammatory responses and gliosis in the etiology of AMD.